Development of Mathematics E-Comic to Facilitate the Mathematical Communication Ability - Risky Kurniawati; Raekha Azka (Hipotenusa : Journal of Mathematical Society, 2022)
This study aims to develop a valid mathematics e-comic learning media for class VIII students on statistical material. The design of the e-comic mathematics learning media development using the PPE stage includes planning (planning), production (production), and evaluation (evaluation). The criteria for achieving quality are carried out by testing so that they are declared valid by experts. The results showed that the e-comic learning media for class VIII students on statistics material for class VIII students on statistics material met the valid criteria. Product validity was obtained based on the assessment of experts which showed that the quality of the learning media was included in the very good category with an average score of 3.65 by the material expert validator, and was included in the very good category with an average score of 3.75 by the media expert validator. Based on the results of the assessment, it can be concluded that the e-comic learning media for class VIII students on statistical material is valid.